Plexiform schwannoma of the rectum. Issue 1 (26th December 2012) - Kawaguchi, Shinya; Yamamoto, Rei; Yamamura, Mitsuhiro; Oyamada, Jun; Sato, Hyoe; Fuke, Hirofumi; Yabana, Tadashi
<x xml:space="preserve">Abstract</x> Plexiform schwannoma is a benign peripheral nerve sheath tumor composed exclusively of Schwann cells arranged in a plexiform pattern. Most plexiform schwannomas are skin tumors and visceral localization is very rare. To our knowledge, there are six cases localized in visceral organs. We describe herein the first known case of plexiform schwannoma of the rectum resected by endoscopic submucosal dissection (ESD). A 77‐year‐old woman presented with a short history of anal pain. Sigmoidoscopy demonstrated a submucosal tumor, 20 mm in diameter, of the rectum below the peritoneal reflection (Rb). We resected the tumorby ESD. The tumor consisted of multiple white nodules in the submucosal layer. Microscopic examination revealed that the tumor was composed mainly of Antoni A tissue, compatible with conventional schwannoma. Immunohistochemically, the tumor was positive for S‐100, and negative for α‐smooth muscle actin, c‐kit and CD‐34. No evidence of recurrence has been found in 2 years of follow up.